ASSESSMENT OF STRESS-STRAIN STATE IN ARARAT SEYSMOPOLIGONE BY MEANS OF $V_P /V_S$ (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
The process of collecting, organizing, filtering and computer background database, the definition of the velocity parameters of seismic waves for assessment of stress-strain state in Ararat seysmopoligone are presented. The errors of calculated parameters (VP/VS) and the statistical analysis of the mean velocity parameters for all the stations of seismic network of RA are evaluated. The average of the Ararat range is clarified and statistical hypothesis testing compliance with the calculated real value is performed.